Corporate Hierarchies and the Size of Nations: Theory and Evidence - Dalia Marin; Thierry Verdier (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2006)
Corporate organization varies within a country and across countries with country size. The paper starts by establishing some facts about corporate organization based on unique data of 660 Austrian and German corporations. The larger country (Germany) has larger firms with flatter more decentral corporate hierarchies compared to the smaller country (Austria). Firms in the larger country change their organization less fast than firms in the smaller country. Over time firms have been introducing less hierarchical organizations by delegating power to lower levels of the corporation. We develop a theory which explains these facts and which links these features to the trade environment that countries and firms face. We introduce firms with internal hierarchies in a Krugman (1980) model of trade. We show that international trade and the toughness of competition in international markets induce a power struggle in firms which eventually leads to decentralized corporate hierarchies. We offer econometric evidence which is consistent with the models predictions.
urn:nbn:de:bvb:19-epub-1346-7
Keywords: F12; F14; L22; D23; 330; international trade with endogenous firm organizations; trade and corporate organization in similar countries; power struggle in the firm; corporate organization in Austria and Germany; empirical test of the theory of the firm; Unternehmensorganisation; Betriebsgröße; Hierarchie; Landesgröße; Theorie; Australien; Deutschland